2010
DOI: 10.2500/ajra.2010.24.3462
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biofilms on Outcomes after Endoscopic Sinus Surgery

Abstract: This study has shown that patients with biofilms have more severe disease preoperatively and persistence of postoperative symptoms, ongoing mucosal inflammation, and infections. This study strengthens the evidence for the role that biofilms may play in recalcitrant CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
143
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 29 publications
4
143
1
5
Order By: Relevance
“…Many studies have indicated that biofilms play important roles in the pathogenesis of CRS and affect the outcomes of endoscopic sinus surgery [9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated that biofilms play important roles in the pathogenesis of CRS and affect the outcomes of endoscopic sinus surgery [9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that bacterial biofilms affect prognosis [11,28]. Some authors reported poorer postoperative CT scores, postoperative symptoms, mucosal outcome, extra postoperative visits, and multiple antibiotic therapy in biofilmpositive patients [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of this disease is often underappreciated, with sufferers having a significantly impaired quality of life. CRS remains a difficult condition to control medically, with a significant number of patients requiring endoscopic sinus surgery [11]. It is well established that biofilm-positive CRS patients are likely to have increased infective exacerbations and slower wound healing and mucosal restoration rates, in addition to a higher level of antibiotic dependence [11].…”
Section: Reactive Oxygen Species As a Novel Adjunctive Biofilm-targetmentioning
confidence: 99%
“…It is well established that biofilm-positive CRS patients are likely to have increased infective exacerbations and slower wound healing and mucosal restoration rates, in addition to a higher level of antibiotic dependence [11]. Staphylococcus aureus biofilms in particular have been identified as one of the main causative agents for chronicity and recalcitrance of the disease [11][12][13].…”
Section: Reactive Oxygen Species As a Novel Adjunctive Biofilm-targetmentioning
confidence: 99%
“…333 Specifically, endpoints of postoperative symptoms, ongoing inflammation, and recurrent infections were all increased in biofilm-positive surgery patients. 323,[334][335][336][337] Biofilm formation in CRS may also be associated with increased need for surgical intervention. Although around 20% of patients with CRS show biofilm formation, 323 up to 50% of CRS surgical candidates are biofilm-positive.…”
Section: Viib Crssnp: Comorbid Asthmamentioning
confidence: 99%